Legal Implications of Credit Deed Agreements Without Legalization at Banks - Renjana, Abhinaya Rai; Taufiq, Muhammad; Hasana, Dahniarti (TABELLIUS: Journal of Law, 2026)
This study aims to analyze the legal force and legal implications of credit agreements without notarial legalization on legal protection for banks and debtors at the Central Java Regional Development Bank. This study uses an empirical legal method with a statutory and sociological legal approach to examine legal provisions normatively and their application in practice. Data were obtained through interviews and observations as primary data, and literature studies as secondary data. Based on the results of the study, it is concluded that credit agreements without notarial legalization remain valid as long as they meet the requirements for a valid agreement according to the Civil Code, but have limitations in evidentiary power and executorial certainty compared to authentic deeds. From the perspective of legal protection, banks as creditors obtain relative protection and depend on internal control mechanisms, while debtors do not receive the guarantee of independent verification as in notarial legalization. This condition indicates implications for the level of legal certainty for parties in credit practices.